2021
DOI: 10.9734/ijpss/2021/v33i1830582
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Drought Stress Treatment on Some Grain Quality Traits in Wheat (Triticum aestivum L.) Varieties

Abstract: Climate change imposes many environmental stresses out of which drought stress is a major concern that significantly restricts crop production in arid and semi-arid regions. The negative impact on grain quality caused by drought stress is responsible for reduced grain yield and quality. Many previous studies aimed to understand the tolerance level of wheat varieties, but studies on grain quality traits assessment were less. Therefore, the aim of the present investigation was to study some grain quality traits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
1
0
0
Order By: Relevance
“…This result agrees with what was mentioned by [49], which indicated that if the wheat crop is exposed to drought and high temperatures, this leads to the appearance of shrunken and wrinkled grains with low specific weights, and thus leads to a decrease in the percentage of flour extraction. These results agreed with [50,51], who indicated that drought stress affects the decrease in specific weight of wheat grain. As for the effect of adding the hydrogel and non-adding it, the results and the arithmetic averages ( Table 5) showed that there were significant differences in the specific weight characteristic, as the treatment of adding the hydrogel achieved a significant superiority at a rate of (80.4 kg.hl -1 ) and an increase of (5.5%) , while the treatment of not adding hydrogels recorded an average of (75.9 kg.hl -1 ).…”
Section: Specific Weight (Kg Hectoliter -1 )supporting
confidence: 92%
“…This result agrees with what was mentioned by [49], which indicated that if the wheat crop is exposed to drought and high temperatures, this leads to the appearance of shrunken and wrinkled grains with low specific weights, and thus leads to a decrease in the percentage of flour extraction. These results agreed with [50,51], who indicated that drought stress affects the decrease in specific weight of wheat grain. As for the effect of adding the hydrogel and non-adding it, the results and the arithmetic averages ( Table 5) showed that there were significant differences in the specific weight characteristic, as the treatment of adding the hydrogel achieved a significant superiority at a rate of (80.4 kg.hl -1 ) and an increase of (5.5%) , while the treatment of not adding hydrogels recorded an average of (75.9 kg.hl -1 ).…”
Section: Specific Weight (Kg Hectoliter -1 )supporting
confidence: 92%
“…Haji et al (2020) documented a progressive correlation between grain protein content and dry and wet gluten content. Generally, significant increases in Zeleny sedimentation index, wet and dry gluten contents, and gluten index showed following stress (Rao et al, 2021).…”
Section: Discussionmentioning
confidence: 95%
“…Several authors recommended that the increase in grain protein percentage due to drought stress in wheat grains may ascribe to reduced starch accumulation (Rao et al, 2021). These effects had a decline in the grain yield and the thousand-kernel weight accompanying them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation